Boarding School Program Management and School Culture on Independent Learning of Students at Junior Boarding School: Manajemen Program Boarding School dan Budaya Sekolah terhadap Kemandirian Belajar Peserta Didik di SMP Boarding School - Febbianti Widia Santoso; Eni Fariyatul Fahyuni (Academia Open, 2022)
This study aims to determine the management of the boarding school program and school culture implemented at SMP Muhammadiyah 9 Tanggulangin Boarding School This research is a descriptive study that aims to describe and analyze the management of the boarding school program and the school culture that forms the learning independence of students at SMP Muhammadiyah 9 Boarding School Tanggulangin. The approach used is a qualitative approach seen from data collection techniques using observation, interviews, and documentation. The results of this study indicate that the management of the boarding school program and school culture implemented at SMP Muhammadiyah 9 BS Tanggulangin is packaged into a set of activities that have been determined by the school principal for student affairs into daily activities that must be carried out by all students starting at 03.30 WIB. Implementation of boarding school programs and school culture that leads to the formation of independent learning for students by providing additional classes outside of school lessons, namely specialization classes and dormitory activities taken from the institution's flagship programs, namely, tahfidz classes, interpretation classes, and language classes. The challenges faced during the implementation of the boarding school program and school culture are: parents are still unfamiliar with the boarding school program and are excessively worried because they see crowded activities, the school environment does not support the implementation of the boarding school program and school culture and the diverse backgrounds of students. Opportunities that can be found after implementing the boarding school program and school culture are: students can form their independence and are able to adapt to the community and the environment they are placed in, have independence in learning, and have self-awareness to complete all responsibilities in learning.